Ujian aptitud sebagai pengukur kebolehpasaran mahasiswa sains sosial - Nik Hairi Omar,; Rusyda Helma Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aptitude test that uses psychometric assessment has been widely used by most employers around the world during a recruitment process to predict candidate abilities in the numerical, verbal, abstract, space and concentration. Given its importance as a job predictor for fresh graduates, this paper investigates the level of aptitude achievement among finals year social science students. This paper also compares the results of aptitude achievement based on the student socio-demographic background such as gender, ethnicity, CGPA and job interests. A total of 88 FSSK students from various programs were randomly selected in the sample conducted in March 2012. A set of measurement instruments containing 30 aptitude questions developed by researchers using an existing questionnaire’s benchmarks modified from the Aptitude Test Psychometric Success for Graduate (ATPSG) 2010. Findings show that the mastery level of all aptitude questions among the respondents is deficient and fails to exceed the minimum passing score of 60 per cent. Test results also showed that the achievement of aptitude did not differ significantly based on gender factors (t= -126, k =>0.05), ethnicity (t = -.462, k =>0.05), area of origin (t= 1.832, k =>0.05), job interest (t = -.188, k =>0.05) and CGPA (t=1.545, k => 0.05). This paper concludes graduate students are having a very low score of aptitude tests and recommending the tests be used as a speciality test at universities for preparatory readiness.